An Analysis of Destructive Fishing as an Anthropogenic Disaster in Coastal Areas: A Maritime Security Perspective - Dao, Yunias; Yusnaldi, Yusnaldi; Kusuma, Kusuma (Nation State: Journal of International Studies, 2024)
Destructive fishing has emerged as a critical threat to maritime ecosystems, posing severe risks to the economy, ecosystem sustainability, resource management, and national security, along with its complex cross-sectoral impacts in coastal areas. As a form of illegal fishing, its harmful consequences necessitate comprehensive scrutiny. This research aims to categorize destructive fishing as an anthropogenic disaster from a maritime security perspective, emphasizing its broad cross-sectoral effects. Employing a qualitative methodology alongside an extensive literature review, this study integrates disaster and maritime security theories, supported by relevant case studies, to thoroughly investigate the issue. The findings reveal that destructive fishing practices qualify as non-natural or anthropogenic disasters, with impacts directly stemming from human activities. These practices damage marine resource ecosystems, disrupt economies, compromise human security, and threaten national security in coastal regions. The study concludes that destructive fishing constitutes an anthropogenic disaster, demanding an urgent, coordinated response from multiple stakeholders. This research advocates for the development and implementation of policies that address the technical dimensions of maritime security, integrate disaster management strategies, and incorporate anthropological insights. Such policies are essential for devising and executing sustainable solutions to this pervasive issue on a global scale.